Relationship between reaction time and performance in the 60 m hurdles at the 2022 World Indoor Championships - Milan Matić; Vladimir Mrdaković (Exercise and Quality of Life)
Previous studies indicate that there is a large influence of the starting reaction time (RT) on sprint performance, but also that some recent changes in athletic rules may affect this correlation. This study aimed to examine the relationship between RT and results in: men’s (M60mH) and women’s (W60mH) disciplines 60 m over hurdles, 60 m hurdles in the heptathlon (H), 60 m hurdles in the pentathlon (P) at the recently held World Indoor Championship 2022 (WIC). The aim was also to determine whether there are differences in RT between M60mH and W60mH, M60mH and H, W60mH, and P, and between H and P. The study included 170 competitors who competed at the WIC. Pearson’s linear correlation coefficient (r) was used for correlation analysis, and the t-test for independent samples was used to examine differences between groups. A statistically significant correlation (r=0.23, N=72, p=0.05) was found between the results and RT in W60mH when observing the entire sample of participants (r2 = 5.29). Considering that in H (r=0.42, N=10, p=0.23, r2=0.18) and P (r=0.54, N=12, p=0.07, r2=0.29), a much higher correlation was obtained between results and RT than in competitors in the 60 m hurdles event, we believe that this is a consequence of different athletic rules that refer to a false start. There are no significant differences between RT for M60mH and W60mH, M60mH and H, W60mH, and P, and between H and P. Coaches should pay attention to developing all parts of the sprint race, including the reaction time.